When do errors in reinforcer delivery affect learning? A parametric analysis of treatment integrity. Issue 2 (24th January 2021) - Bergmann, Samantha; Kodak, Tiffany; Harman, Michael J.
Abstract : Treatment integrity is the extent to which components of an intervention are implemented as intended (Gresham, 1989). Recent behavior‐analytic literature has begun to evaluate the effects of reduced‐treatment integrity on the efficacy and efficiency of skill‐acquisition interventions. This study extended the current literature on the effects of errors of omission and commission of reinforcer delivery by replicating and extending Hirst and DiGennaro Reed (2015). Using a randomized‐control group design, we compared undergraduate student participants' acquisition of conditional discriminations in a parametric analysis of different error values. A computer program erred in reinforcer delivery on 0%, 5%, 10%, 15%, 20%, 25% and 50% of trials. The purpose of the current study was to identify which levels of reduced integrity slowed or prevented acquisition. Our data replicated the findings of Hirst and DiGennaro Reed, and extended parametric analyses by identifying that errors in reinforcer delivery occurring on 15% or fewer trials (i.e., 85% integrity) were unlikely to prevent participants' responding from meeting the mastery criterion. These results could inform future research on how treatment‐integrity errors change behavior‐analytic procedures and the effects on skill acquisition for consumers of applied behavior analysis.